학문 목적 한국어 고급 학습자의 발표 담화에 나타난 응결 장치 실현 양상 연구 - 하지혜; 황선영 (이중언어학, 2018)
This study analyzes the presentation test given by advanced Korean language learners to examine discourse cohesion shown upon using cohesive device. It focuses on the use of grammatical and lexical devices as a cohesive device. The data collected included a total of 20 people, which amounted to about three hours per 9,967 words. The analysis is confined to the use of conjunction, reference, substitution, same word, synonym, antonym, superordinate/hyponymy among cohesive devices of discourse. As a result, learners have mainly used ‘conjunction’, only a few ‘reference’ and few ‘substitution’ have been used. And the learners showed a limitation of focusing on the repetition of words without having to use a variety of lexical devices. Through this discussion, the study was able to identify the condensation systems needed for academic learners. The study confirmed that academic learners of Korean language are not able to use a variety of cohesive devices as they appear in presentations. Therefore, it should be taught more actively at the teaching site.
Keywords: Korean for Academic purpose leaners; Presentation; Discourse; Cohesion; Coherence; Cohesive device; 학문 목적 한국어 학습자; 발표; 담화; 응결성; 응집성; 응결 장치